Sex- and age-specific reference intervals of 16 steroid metabolites quantified simultaneously by LC-MS/MS in sera from 2458 healthy subjects aged 0 to 77 years - Frederiksen, Hanne; Johannsen, Trine Holm; Andersen, Stine Ehlern; Petersen, Jørgen Holm; Busch, Alexander Siegfried; Ljubicic, Marie Lindhardt; Fischer, Margit Bistrup; Upners, Emmie N.; Hagen, Casper P.; Main, Katharina M.; Aksglaede, Lise; Jørgensen, Niels; et al. (Clinica chimica acta, 2024)
•A novel, specific, and sensitive isotope diluted LC-MS/MS method was developed for simultaneous quantitation of 16 steroid hormone metabolites.•Steroid metabolites in serum from healthy infants, children, adolescents, and adults aged 0.17 months to 77 years (n = 2458) were analysed.•Sex- and age specific reference intervals of 15 steroid metabolites were established. Reference intervals covering the whole life span for all the metabolites in the steroid hormone biosynthesis quantified by sensitive and robust analytical methods are sparse or not existing. To develop a state-of-the-art LC-MS/MS method for simultaneous quantification of multiple steroid metabolites and to establish detailed sex- and age-specific reference intervals for 16 steroid metabolites. An isotope diluted LC-MS/MS method was developed for simultaneous quantitation of 16 steroid hormones. Serum samples from cross-sectional cohorts of healthy infants, children, adolescents, and adults aged 0.17 months to 77 years (n = 2458) were analysed. With this novel, specific, and sensitive LC-MS/MS method, it was possible to quantify progesterone, 17-hydroxypregnenolone, 17-hydroxyprogesterone, dehydroepiandrosterone sulfate, androstenedione, testosterone, dihydrotestosterone, 11-deoxycorticosterone, corticosterone, 11-deoxycortisol, cortisol, and cortisone in ≥90 % of the samples, while estrone sulfate, aldosterone and dehydroepiandrosterone were quantified in 77 %, 75 % and 60 % of the samples, respectively. 21-deoxycortisol was only detectable in 2.5 % of samples from healthy subjects. Sex- and age-dependent fluctuations observed in minipuberty, puberty and adulthood including the menopausal transition were modelled. This enabled us to establish valid reference intervals from birth to late adult life for both males and females. Detailed sex- and age-specific reference intervals of multiple, simultaneously quantified steroid metabolites by a novel and specific LC-MS/MS method provides a valuable tool for clinical practice and for future research.